Hyperbolic Functions: X X - LX X 0 L
Hyperbolic Functions: X X - LX X 0 L
e x - e -x e x + e -x
definition sinhx = coshx =
2 2
4
0
symmetry sinh(-x) = -sinhx cosh(-x) = coshx
† †
-1
† †
special equation
general solution †
derivative of general solution †
Ï l>0 Ï c 1 le l x - c 2 le - lx l>0
c 1e lx + c 2e - l x Ô
Ô
X(x) = Ì c 1 + c 2x l=0 X¢(x) = Ì c2 l=0
Ôc cos -lx + c sin -lx l<0 Ô-c -l sin -lx + c -l cos -lx l<0
Ó 1 2 Ó 1 2
† †
† †
Ïc cosh lx + c sinh lx Ï c l sinh lx + c l cosh lx l>0
Ô 1 2 l>0 Ô 1 2
† †
† †
Ïc cosh l x - x + c sinh l x - x Ï c l sinh l x - x + c l cosh l x - x l>0
Ô 1 ( 0) 2 ( 0) l>0 Ô 1 ( 0) 2 ( 0)
X(x) = Ì c 1 + c 2 (x - x 0 ) l=0 X¢(x) = Ì c2 l=0
Ô Ô-c -l sin -l x - x + c -l cos -l x - x l<0
Óc 1 cos -l (x - x 0 ) + c 2 sin -l (x - x 0 ) l<0 Ó 1 ( 0) 2 ( 0)
† †
† †